Behavioral economics and the experimental analysis of costume behavior - Montgomery Urday, William (2011)
This paper considers the contribution of the experimental analysis of behavior in the context of development of behavioral economics, and its complementarity with current research in economic psychology. First, we review the origins and development of behavioral economics from the basic principles underlying the law of marginal utility in relation to states of deprivation and satiation behavior, the role of the token economy and regulation behavior. Secondly, we discuss studies on the subject of the relationship between behavioral economics and decision-making consumer behavior, concluding that prove useful for evaluating conceptual countless situations applied.